Good products, bad products : essential elements to achieving superior quality - Adams, James (McGraw-Hill, 2012)
Featuring case studies of famous brands that became victims of their own success like Kodak; IBM; Zenith; and GM; this provocative book provides a brilliant; in-depth look at the powerful but elusive qualities that can make or break a products success. --